Dereplicating nonribosomal peptides using an informatic search algorithm for natural products (iSNAP) discovery - Ibrahim, Ashraf; Yang, Lian; Johnston, Chad; Liu, Xiaowen; Ma, Bin; Magarvey, Nathan A (Proceedings of the National Academy of Sciences - PNAS, 2012)
Nonribosomal peptides are highly sought after for their therapeutic applications. As with other natural products, dereplication of known compounds and focused discovery of new agents within this class are central concerns of modern natural product-based drug discovery. Development of a chemoinformatic library-based and informatic search strategy for natural products (iSNAP) has been constructed and applied to nonribosomal peptides and proved useful for true nontargeted dereplication across a spectrum of nonribosomal peptides and within natural product extracts.